Epitope mapping of neutralising anti‐SARS‐CoV‐2 monoclonal antibodies: Implications for immunotherapy and vaccine design. (8th April 2022) - Ghotloo, Somayeh; Maghsood, Faezeh; Golsaz‐Shirazi, Forough; Amiri, Mohammad Mehdi; Moog, Christiane; Shokri, Fazel
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is the causative agent of the coronavirus disease 2019 (COVID‐19) pandemic. This disease has currently affected more than 346 million people and resulted in more than 5.5 million deaths in many countries. Neutralising monoclonal antibodies (MAbs) against the SARS‐CoV‐2 virus could serve as prophylactic/therapeutic agents in COVID‐19 infection by providing passive protection against the virus in individuals. Until now, no Food and Drug Administration/European Medicines Agency‐approved neutralising MAb against SARS‐CoV‐2 virus exists in the market, though a number of MAbs have been authorised for emergency use. Therefore, there is an urgent need for development of efficient anti‐SARS‐CoV‐2 neutralising MAbs for use in the clinic. Moreover, neutralising anti‐SARS‐CoV‐2 MAbs could be used as beneficial tools for designing epitope‐based vaccines against the virus. Given that the target epitope of a MAb is a crucial feature influencing its neutralising potency, target epitopes of neutralising anti‐SARS‐CoV‐2 MAbs already reported in the literature and reactivity of these MAbs with SARS‐CoV‐2 variants are reviewed herein.